2012
DOI: 10.1177/2151458513477108
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Fibular Strut Allograft in an Osteoporotic Distal Humerus Fracture

Abstract: In 2004, nearly 120 000 fragility fractures of the humerus were reported. As the US population ages, this number is expected to increase. Fractures of the distal humerus can be treated in a closed or open fashion. Open treatment includes open reduction and internal fixation or total elbow arthroplasty. Open reduction and internal fixation typically involves dual plating for increased stability and early mobility. We present a case in which dual plating failed due to lack of screw purchase in osteoporotic bone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We also noted a robust effect of iNOS inhibition or knockdown on in vitro colony formation by human melanoma cells, suggesting that even in vitro iNOS may be required for optimum clonogenicity of founder cells. We also found that exogenously-supplied NO reverses mTOR pathway inhibition seen after Vemurafenib treatment, suggesting that NO can act downstream of BRAF to bypass BRAF inhibition, and thus is a potential mechanism of escape (44, 45)…”
Section: Discussionmentioning
confidence: 68%
“…We also noted a robust effect of iNOS inhibition or knockdown on in vitro colony formation by human melanoma cells, suggesting that even in vitro iNOS may be required for optimum clonogenicity of founder cells. We also found that exogenously-supplied NO reverses mTOR pathway inhibition seen after Vemurafenib treatment, suggesting that NO can act downstream of BRAF to bypass BRAF inhibition, and thus is a potential mechanism of escape (44, 45)…”
Section: Discussionmentioning
confidence: 68%
“…Fibular strut allografting has been reported to provide immediate and long-term stability in the treatment of comminuted fractures of different long bones such as the humerus [7,15]. We have been using fibular strut grafts to treat UBCs in patients with a closed physis for several years.…”
Section: Introductionmentioning
confidence: 99%
“…A fibular strut allograft was then used to compensate for this fracture. The results of this operation showed that the patient was able to work without pain after three months, and after 6 months, the fracture completely healed through radiographic diagnosis 18 .…”
Section: Discussionmentioning
confidence: 91%